2012
DOI: 10.1590/s0102-695x2011005000206
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated fucans extracted from algae Padina gymnospora have anti-inflammatory effect

Abstract: Sulfated polysaccharides were extracted with acetone from brown algae Padina gymnospora. The fraction precipitated with 1.5 volumes of acetone (F1.5) purified in Sephadex G-75 was characterized by infrared and nuclear magnetic resonance of 13 C and 1 H, through which the presence of sulfate groups on the C4 of α-L-fucose could be observed. This polysaccharide showed that an MW of 25,000 Da was effective in reducing leukocyte influx into the peritoneal cavity in mice at 10 mg/kg and 25 mg/kg body weight, causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
(40 reference statements)
0
9
0
2
Order By: Relevance
“…The results revealed a typical pattern for C. cervicornis , which did not vary according to the geographical region [25]. From Padina gymnospora (source of A3) only few metabolites classes were isolated until now, such as fatty acids [48], and sulfated polysaccharides [49]. From Palisada perforada (source of A8) only two triquianes alcohols compounds were described [50].…”
Section: Resultsmentioning
confidence: 83%
“…The results revealed a typical pattern for C. cervicornis , which did not vary according to the geographical region [25]. From Padina gymnospora (source of A3) only few metabolites classes were isolated until now, such as fatty acids [48], and sulfated polysaccharides [49]. From Palisada perforada (source of A8) only two triquianes alcohols compounds were described [50].…”
Section: Resultsmentioning
confidence: 83%
“…Brown-algal fucoidans possess a broad spectrum of biological activities, including anti-coagulant (Cumashi et al 2007), hypolipidemic (Yokota et al 2009;Cuong et al 2015), anti-thrombotic (Boisson-Vidal et al 2000;Mourao 2004;Drozd et al 2011), anti-inflammatory (Cl ement et al 2010Marques et al 2012;Pomin 2015), immunomodulatory , anti-adhesive (Cumashi et al 2007) and anti-hypertensive properties (Xueyan et al 2004); these molecules may exert an influence on numerous targets in the context of atherosclerosis therapy.…”
Section: Therapeutic Targets For Fucoidan In Atherosclerosismentioning
confidence: 99%
“…A number of authors have reported a decrease in leukocyte migration into the inflammatory zone after intravenous injection of fucoidan from Laminaria saccharina, Laminaria digitata, Fucus evanescens, Fucus serratus, Fucus distichus, Fucus spiralis, Ascophyllum nodosum (Cumashi et al 2007), Padina gymnospora (Marques et al 2012), sulfated galactofucan from Lobophora variegate (Medeiros VP et al 2008). It has been established that fucoidan directly bound to CD11b/CD18 in a divalent cation-and sulfation-dependent fashion (Zen et al 2002).…”
Section: L-and P-selectin Cd11b/cd18mentioning
confidence: 99%
See 1 more Smart Citation
“…SPS are also characterized by the antiinflammatory effect [36,85,86]; in this context, they may be consid ered as a useful supplement in the therapeutic schemes treatment of infections caused by herpesviruses. Finally, the antioxidant properties of these unique compounds are described in numerous reports [30,87,88] and they can make a certain contribution to the therapy of patients with herpesvirus infections.…”
Section: Immunomodulatory Antiinflammatory and Antioxidant Effects Omentioning
confidence: 99%